Manufacturing technology : materials, processes, and equipment - Youssef, Helmi A.; El-Hofy, Hassan; Ahmed, Mahmoud H. (Boca Raton, FL : CRC Press, 2012)
'This text explores all of the manufacturing processes, materials, and equipment used to convert raw materials into a final product. It presents the most commonly used and recently developed manufacturing methods, along with applications, worked examples, exercises, and review questions. Materials covered include metallics, polymers, ceramics, and glasses. The book discusses heat treatments, smelting of metals, process casting, forming, powder metallurgy, joining processes, and surface technology. It also looks at the environmental aspects related to manufacturing and clean factories and describes trends in surface hardening technology'--
'The textbook in hand provides a comprehensive knowledge and insight into various aspects of manufacturing technology, processes, materials, tooling, and equipment. Its main objective is to introduce the brand spectrum of manufacturing technology to individuals who will be involved in design and manufacturing of finished products, to provide them with the basic information on manufacturing technologies. The text material is presented mainly in descriptive manner, where the emphasis is on the fundamentals of the process, its capabilities, typical applications, advantages and limitations. Mathematical modeling and equations are used only when they enhance the basic understanding of the material dealt with'--
Includes bibliographical references and index.
Keywords: Manufacturing processes